Acute Diarrheal Management in Adults: A Simulated Client Study at Community Pharmacies of Quetta City, Pakistan - Khan, Asad; Iqbal, Qaiser; Haider, Sajjad; Khalid, Adnan; Azmi Hassali, Mohamed; Saleem, Fahad (Journal of Pharmacy Practice and Community Medicine)
Objective: By using a simulated client approach, we aimed to assess the management of acute diarrhea in adults at community pharmacies in Quetta City, Pakistan. Methods: This was a cross sectional, simulated client study. The study was carried out in Quetta, the provincial capital of Balochistan province, Pakistan. Community pharmacies located in the urban region with more than 100 clients per day were targeted for data collection. The simulated client presented himself at the community pharmacies seeking treatment for acute diarrhea with a pre-planned discussion protocol. SPSS v 21.0 was use for data analysis. Based on the objectives of the study, data was described descriptively as frequencies and percentages. Results: A total of 185 pharmacies qualified for the study as per inclusion criteria but data was available from 155 CPs (83.7%). The average working hours for the CPs were fourteen while qualified pharmacist was only present in fifteen (9.6%) of the pharmacies. The consultation time at the pharmacies ranged from 1-4 mins with a mean of 2.37±0.535 mins. Tablet metronidazole was the most frequent medicine dispensed (78.1%) at the CPs. Dimenhydrinate was dispensed (41.3%) followed by Oral Rehydration Solution (ORS) and tablet domperidone (35.5 and 25.8%) respectively. Minimum cost of medicine dispensed ranged from 10 Pakistan Rupees (PKR) i.e. (0.086 USD) to 960 PKR i.e. (8.30 USD). Conclusion: The management of acute diarrhea failed to meet the standard anti-diarrheal treatment as proposed by the guidelines. Therefore, a substantial improvement of pharmacy practice at the community pharmacies is urgently needed.
Keywords: Acute Diarrheal Management; Community Pharmacies; Quetta; Simulated Client Study